Health inequalities of the Roma in Europe: a literature review - Parekh, Nikesh; Rose, Tamsin (Central European journal of public health, 2011)
The Roma are the most populous marginalised community in Europe and have some of the greatest health needs. There is a higher prevalence of communicable and non-communicable diseases within the community and significantly shorter life expectancies than national averages. Efforts by governments across Europe to address these health inequalities have been relatively weak and the Roma suffer poorer access to health care, education and employment in every country that they inhabit in comparison to the majority population. As the socioeconomic determinants of health become better understood over the past decade, it is becoming clear that societies with greater inequalities are less healthy overall. It is important for public health across Central and Eastern Europe that the health needs of the Roma are prioritised by governments concerned. We provide a review of the literature on the health inequalities of the Roma community in Europe.
Keywords: dostupnost zdravotnických služeb; předsudek; Socioeconomic Factors; Prejudice; Health Status Disparities; Romové; Roma; disparity zdravotního stavu; Health Services Accessibility; Humans; lidé; chudoba; Europe; Poverty; Evropa; socioekonomické faktory; Healthcare Disparities; disparity zdravotní péče